Measuring and understanding the effects of a performance based financing scheme applied to nutrition services in Burundi—a mixed method impact evaluation design. Issue 1 (December 2016) - Nimpagaritse, Manassé; Korachais, Catherine; Roberfroid, Dominique; Kolsteren, Patrick; Zine Eddine El Idrissi, Moulay; Meessen, Bruno
Abstract Background Malnutrition is a huge problem in Burundi. In order to improve the provision of services at hospital, health centre and community levels, the Ministry of Health is piloting the introduction of malnutrition prevention and care indicators within its performance based financing (PBF) scheme. Paying for units of services and for qualitative indicators is expected to enhance provision and quality of these nutrition services, as PBF has done, in Burundi and elsewhere, for several other services. Methods This paper presents the protocol for the impact evaluation of the PBF scheme applied to malnutrition. The research design consists in a mixed methods model adopting a sequential explanatory design. The quantitative component is a cluster-randomized controlled evaluation design: among the 90 health centres selected for the study, half receive payment related to their results in malnutrition activities, while the other half get a budget allocation. Qualitative research will be carried out both during the intervention period and at the end of the quantitative evaluation. Data are collected from 1) baseline and follow-up surveys of 90 health centres and 6, 480 households with children aged 6 to 23 months, 2) logbooks filled in weekly in health centres, and 3) in-depth interviews and focus group discussions. The evaluation aims to provide the best estimate of the impact of the project on malnutrition outcomes in the community as well as outputs at the health centre level (malnutrition care outputs) and to describe quantitatively and qualitatively the changes that took place (or did not take place) within health centres as a result of the program. Discussion Although PBF schemes are blooming in low in-come countries, there is still a need for evidence, especially on the impact of revising the list of remunerated indicators. It is expected that this impact evaluation will be helpful for the national policy dialogue in Burundi, but it will also provide key evidence for countries with an existing PBF scheme and confronted with malnutrition problems on the appropriateness to extend the strategy to nutrition services. Trial registration ClinicalTrials.gov PRS Identifier:NCT02721160 ; registered March 2016